The Influence Of Feeding Practices On Nutritional Status Of Children Less Than 2 Years In Heliwa District, Mogadishu - Dahie, Hassan Abdullahi; Heyle, Abdullahi Ali (Advances in Social Sciences Research Journal, 2017)
Background: Adequate nutrition during infancy and early childhood is fundamental to the development of each child’s full human potential. A child who has adequate nutrition performs better in school, grows into a healthy adult and in turn gives his/her children a better start in life. However, for a child to have an adequate nutrition basically depends on the feeding practices offered by mothers or care-takers (UNICEF, 2007). SDG 2 is targeted at improving nutrition, ending hunger and achieving food security. Objective: To determine the influence of feeding practices on nutritional status of children under two years in Heliwa District, Mogadishu, Somalia 2016. Methodology: Community-based cross sectional study design. Data were collected by using pretested questionnaires. A total of 403 mothers and their children were included in the study. A systematic random sampling and simple random sampling were used to select the households to participate and starting household respectively. Data were captured using EpiData-3.0, excel and ENA, analysed with STATA-12. Univariate and bivariate analysis were carried out to see significant association, a P-value <0.05 was considered as significant association. Results: The prevalence of underweight, stunting and wasting were 30.7%, 27.5% and 28.5% respectively. Children whose fathers were unemployed were 2 times more likely to develop wasting than employed (OR 2.0, 95%CI 1.42-2.88). Furthermore, children who were introduced complementary foods late after six months were more likely to develop underweight and wasting [(OR 1.59 95%CI 1.22-2.92) and (OR 1.40 95%CI 1.09-2.43)] respectively. Conclusion and recommendation: There was high prevalence of malnutrition (wasting, stunting and underweight) among children less than 2 years in the district. There is a need for intervention programs. Midwives and nurses should encourage mothers to initiate breastfeeding in the first hour after delivery.